2021
DOI: 10.2147/rmhp.s295806
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Incomplete Vaccination Among Children Aged 12 to 23 Months in Gindhir District, Southeastern Ethiopia: Unmatched Case–Control Study

Abstract: Background: Incomplete vaccination can put children at greater risk of acquiring vaccinepreventable diseases. In Ethiopia, vaccination coverage against vaccine-preventable diseases is still a significant and persistent public health challenge. Thus, the aim of this study was to identify the determinants of incomplete childhood vaccination among children aged 12-23 months in Gindhir District, Southeast Ethiopia. Methods: A community-based unmatched case-control design was employed among children aged 12-23 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…Hence, children born to younger women were more likely to have incomplete vaccination against polio compared to those born to older women. This finding is consistent with the findings of studies that have been carried out in Ethiopia [26,27] and other low-and middle-income countries [28][29][30][31], which found that young maternal age is a risk factor for incomplete childhood immunization. The possible reason for the finding could be the better understanding of the child's health and the importance of vaccination among older women compared to younger women [30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, children born to younger women were more likely to have incomplete vaccination against polio compared to those born to older women. This finding is consistent with the findings of studies that have been carried out in Ethiopia [26,27] and other low-and middle-income countries [28][29][30][31], which found that young maternal age is a risk factor for incomplete childhood immunization. The possible reason for the finding could be the better understanding of the child's health and the importance of vaccination among older women compared to younger women [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…Children of mothers with a higher educational level and wealth index were less likely to be incompletely immunized against polio compared with those with no formal education. High socio-economic status (wealth and educational level) has been found to be protective against incomplete childhood vaccination in several studies in low-and middle-income countries, including Ethiopia [26][27][28][29][30][31]. In explaining the relationship between socio-economic status and childhood vaccination, several authors have explained that higher socio-economic status enhanced health-care seeking for child health, including immunization [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The highest coverage of full vaccination in Addis Ababa (83%) and lowest in Afar region due to different challenges and opportunities as explained in other studies (20%) (5,13). Studies have also reported that maternal education, place of delivery, antenatal care (ANC) visits, postnatal care follow up, place of residence and exposure to mass media as predictors of poor child immunization status (13,14,17,19). However, most of the studies were cross-sectional and failed to include certain variables or factors that could be pertinent in the Ethiopian context, such as socioeconomic status, attitude and service satisfaction towards immunization services provision at grassroots of individual family members and few community-based studies are available.…”
Section: Introductionmentioning
confidence: 83%
“…The full vaccination coverage has been raised from 39% in 2016 to 43% in 2019 EDHS report and about 19% children in 12-23months age group have not received any vaccinations at all (16). The highest coverage of full vaccination in Addis Ababa (83%) and lowest in Afar region due to different challenges and opportunities as explained in other studies (20%) (5,13). Studies have also reported that maternal education, place of delivery, antenatal care (ANC) visits, postnatal care follow up, place of residence and exposure to mass media as predictors of poor child immunization status (13,14,17,19).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation